The entrepreneurial opportunity of the second-generation ethnic entrepreneurs: The case of Vietnamese immigrants in Germany - Cat My Dang (My University, 2019)
The entrepreneurial opportunity of the second-generation ethnic entrepreneurs: The case of Vietnamese immigrants in Germany
Keywords: Ethnic entrepreneurs